Manufacture of Fish Feed and Animal Feed by Utilizing Waste from Livestock Manure as an Alternative for Community Livelihoods in Bekiung Village, Kuala District, Langkat Regency, North Sumatra Province - Hasibuan, Julia Syahriani; Khairunnisa; Wahyuni, Hafnes (Talenta Publisher, 2023)
BUMDesa Bangun Mandiri in Bekiung village, Kuala sub-district, Langkat district, is that raising cattle is still carried out traditionally without considering the processing of livestock manure. In addition to the problems caused by livestock waste, the high price of feed produced by feed factories will reduce the profits obtained by the surrounding community, especially fish cultivators. This community service activity was carried out in Bekiung Village, Kuala District, Langkat Regency, North Sumatra Province. Methods Implementation of activities is carried out through approaches with several methods, such as the formation of implementing committee team is carried out through a family discussion approach, handing over tools and materials for making feed, outreach, and practical training in making animal feed and fish to marketing/selling products and services through social media, as well as providing service activity modules.